Pengembangan Media Pembelajaran (Trainner) Kontrol Motor Listrik Pengasutan Bintang-Segitiga Dengan Programmable Logic Controller (PLC) Pada Mata Pelajaran Instalasi Motor Listrik - Made Agus Wahyu Dwi Kusuma; Agus Adiarta; I Gede Ratnaya (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This research aims to 1) make a star-triangle starting electric motor control trainer with a Programmable Logic Controller (PLC) 2) determine the feasibility, 3) as well as knowing the response of students to the Learning Media (TraiTrainerntrol of a Triangle Star-Starting Electric Motor with a Programmable Logic Controller (PLC) in the subject of Electrical Motor Installation (IML). This study uses a Research and Development (R&D) research and development method. Data collection in this study was carried out by distributing questionnaires or questionnaires which were assessed by the content or material experts, media experts, and students. The results obtained: the results of the validation test from media experts get a percentage of 91.66% including very feasible qualifications, the results of the content or material expert validation test get a percentage of 94.00% including very feasible qualifications, the results of the small group trial score range with 8 respondents all included in the category of strongly agree, and the results of the large group test score range with 25 respondents all categorized as strongly agree. Based on the results of the research, the Learning Media Trainer of Electric Motor Control with a Programmable Logic Controller (PLC) is suitable for use in the learning process of Electric Motor Installation (IML).